Pengaruh Citra Perusahaan Dan Persepsi Harga Terhadap Loyalitas Nasabah Dengan Mediasi Kepercayaan Nasabah (Studi Pada Nasabah Bni Life Regional Office Semarang) - I Dewa Gede Alit Suwardhana Putra; Endang Tjahjaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research is a literature review that analyzes the influence model of corporate image and influencer endorsement on customer loyalty through customer trust. The focus of research on customer loyalty BNI Life Regional Office Semarang is based on research gaps that arise from previous research, namely: Budiyanti's research, (2023) concluded, there is a positive influence between customer trust on customer loyalty, but Tandiwijaya and Pusparini, (2022) did not show a significant effect of customer trust on customer loyalty. Based on this research gap, this research on BNI Life Regional Office Semarang tends to support Budiyanti's research, (2023) which states that customer trust has a positive effect on customer loyalty. The phenomenon gap in this study is that there was a decrease in both the number of policies and the number of agents in 2016-2018 and the 2019-2022 period due to reduced agents and customer loyalty to BNI - Life. The results of this study indicate that company image has a positive effect on customer trust and customer loyalty, price perceptions have a positive effect on customer trust and customer loyalty, and customer trust has a positive effect on customer loyalty. Customer trust is able to mediate the effect of company image and price perception on customer loyalty. Suggestions for future research need to add other variables that affect customer loyalty. Suggested variables are: customer experience, brand equity and so on. Future research suggestions need to use comparisons to find out the position of PT BNI Life Insurance Regional Office Semarang with its competitors in increasing customer loyalty, by examining Axa Mandiri, BCA Life and so on.